A rare case of postnatal mosaic trisomy 12 with severe congenital heart disease and literature review. Issue 6 (24th March 2021) - Hu, Xiaolin; Ayala, Sofia Saenz; Dyer, Lisa; Guan, Qiaoning; Pena, Loren
Abstract: Trisomy 12 is a rare autosomal aneuploidy. All postnatally diagnosed individuals with trisomy 12 have been mosaic for this chromosome abnormality. We herein report an infant girl presented at 2 weeks of age with severe congenital heart defect, tracheobronchomalacia, and dysmorphic features. All of the dysmorphic features of this patient fit into the known phenotype spectrum of mosaic trisomy 12, although this patient uniquely presented with macrocephaly. Tracheo‐bronchomalacia has been described once previously but had a significant impact on this patient's clinical course. The patient passed away at 2‐month‐old due to cardiac and respiratory complications. Chromosomal single nucleotide polymorphism (SNP) microarray analysis on a peripheral blood sample from the patient revealed trisomy 12 in approximately 50% of cells. Concurrent fluorescence in situ hybridization analysis of uncultured blood cells detected a comparable level of trisomy 12 mosaicism. Compared to conventional cytogenetics, SNP microarray examines all nucleated cells without sampling bias, has an increased power to estimate mosaicism level, and can provide a quick assessment of the underlying mechanism. Here we demonstrate the utilization of SNP microarray in the clinical diagnosis of those once considered rare disorders but might have been missed by conventional cytogenetic techniques.